Autism Face Detection System using Single Shot Detector and ResNet50 - Melinda Melinda; Muhammad Fauzan Alfariz; Yunidar Yunidar; Agung Hilm Ghimri; Maulisa Oktiana; Rizka Miftahujjannah; Nurlida Basir; Donata D. Acula (LPPM Institut Teknologi Telkom Purwokerto, 2026)
Non-Indexed Publication